2009
DOI: 10.1194/jlr.m800567-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The microsomal cardiolipin remodeling enzyme acyl-CoA lysocardiolipin acyltransferase is an acyltransferase of multiple anionic lysophospholipids

Abstract: Phospholipids are subjected to remodeling through the Lands cycle to attain appropriate FA compositions. In recent years, at least two families of lysophospholipid acyltransferases have been identified. Acyl-CoA lysocardiolipin acyltransferase 1 (ALCAT1) was initially identified as a microsomal lysocardiolipin acyltransferase. However, the physiological relevance of how this enzyme is involved in cardiolipin remodeling has not been elucidated. We report in this study that ALCAT1 possesses acyltransferase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
(49 reference statements)
2
42
0
Order By: Relevance
“…The enzyme activity utilized both MLCL and dilysocardiolipin substrates and exhibited specificity for unsaturated long chain fatty acyl-CoAs. In addition, this enzyme catalyzed the acylation of a host of monoionic lysophospholipids (32,33). This enzyme is likely identical to the acyltransferase first described in rat liver ER (22).…”
Section: Discussionsupporting
confidence: 59%
“…The enzyme activity utilized both MLCL and dilysocardiolipin substrates and exhibited specificity for unsaturated long chain fatty acyl-CoAs. In addition, this enzyme catalyzed the acylation of a host of monoionic lysophospholipids (32,33). This enzyme is likely identical to the acyltransferase first described in rat liver ER (22).…”
Section: Discussionsupporting
confidence: 59%
“…Mammalian LYCAT is reported to possess acyltransferase activity toward the sn -2 position of anionic lysophospholipids including lysoPI, lysoPG, and lysoCL in vitro (17)(18)(19)(20). In this study, we examined the fatty acid composition of each phospholipid from various tissues of LYCAT Ϫ / Ϫ mice, and showed that LYCAT determines the fatty acid composition of PI in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…These results indicate that LYCAT signifi cantly contributes to acyltransferase activity toward the sn -1 position of PI and PG in mouse liver. Furthermore, sn -1-acyl LPIAT activity was reduced by 33% (from 0.15 ± 0.00 to 0.10 ± 0.00 nmol/min/mg protein) and LPGAT activity was reduced by 57% (from ferase activities toward the sn -2 position of PI and PG ( 20 ). sn -1-acyl LPCAT, LPEAT, and LPSAT activities were not altered signifi cantly in the LYCAT Ϫ / Ϫ liver ( Table 1 ).…”
Section: Lycat Defi Ciency Causes Reduced Acyltransferase Activity Tomentioning
confidence: 93%
See 1 more Smart Citation
“…In mammalian cells, two additional enzymes, lysocardiolipin acyltransferase 1 (AL-CAT1) and MLCL acyltransferase 1 (MLCL AT-1), can use acyl-CoAs to esterify MLCL ( 28 ). ALCAT1, however, is located on the ER, which would prevent its interaction with most CL ( 30 ), but MLCL AT-1 is present in mitochondria ( 11 ). Although overexpressing MLCL AT-1 in tafazzindefi cient lymphoblasts increases both linoleate incorporation into CL and total CL content ( 11 ), the importance of MLCL AT-1 for normal CL remodeling in heart cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%